Inhibition of Mild Steel Corrosion in 1N H2SO4 Medium by Acid Extract of Nyctanthes arbortristis Leaves - R. Saratha; V. G. Vasudha (E-Journal of Chemistry)
Efficiency of acid extract of dry Nyctanthes arbortristis (Night Jasmine, Coral Jasmine) leaves as corrosion inhibitor for mild steel in 1N H2SO4 medium was investigated in the present study. Experimental methods include weight loss and polarization studies. The results indicate Nyctanthes arbortristis leaves to be a good corrosion inhibitor of a mixed type and having efficiency as high as 90% at 1% inhibitor concentration.